A Computational Prototype for Electromagnetic Field Pollution Maps in Colombia (2021)
This work presents a first computational prototype for Electromagnetic Field (EMF) pollution visualization, as a geographic map for human exposure estimation to potentially harmful levels of electromagnetic radiation. The map is a computational tool including a mobile application that uses a basic EMF mathematical model for estimating levels of exposure in two geographic dimensions based on a limited collection of antennas information from Bogot´a City. Our application is intended to be an inexpensive first solution for EMF pollution analysis. This paper shows a first mobile prototype as a result, based on standard free tools, such as Google Maps API and its drawing tools and open access EMF emitters databases.